Peran Ukuran Teks dalam Meningkatkan Daya Tarik Promosi Digital - Vanessa Julia Ang (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
Instagram is a widely used visual-based social media platform that serves as an effective medium for digital promotion due to its strong emphasis on imagery and concise communication. In the realm of visual content design, text size functions as a critical typographic element that influences audience attention, message clarity, and overall visual appeal. This study adopts the Design Thinking methodology, consisting of observation, interviews, and design testing stages, to examine how text size affects the attractiveness and communicative strength of promotional content. The findings demonstrate that larger text sizes significantly improve visual focus, enhance readability, and increase user engagement with the presented promotional material. Furthermore, the use of proportional and well-structured text sizes strengthens visual hierarchy, thereby enabling viewers to identify key messages more efficiently. These results underscore that determining an appropriate text size is not merely an aesthetic choice but a strategic component of effective digital promotional design on Instagram. The study highlights the importance of integrating typographic considerations into broader communication strategies to achieve visually compelling, informative, and impactful promotional outputs. It is expected that these insights will contribute to the development of more user-centered and visually optimized digital promotional designs across various creative and marketing practices.